2021
DOI: 10.9734/ajaees/2021/v39i1030709
|View full text |Cite
|
Sign up to set email alerts
|

Yield Gap Analysis of Rapeseed (Brassica campestris var. Toria) in Kokrajhar District of Assam, India

Abstract: The present study was carried out at five different villages of Kokrajhar district of Assam where cluster front line demonstration (CFLD) of High Yielding Variety (HYV) of rape seed (TS 46) was conducted by Krishi Vigyan Kendra, Kokrajhar.  A total of 652 nos. of front line demonstration (FLD)s were evaluated to find out the yield gaps between HYV toria variety TS 46 and variety grown by farmers. Yield data of both demonstration and farmers practice were recorded and their yield gap, technology gap, extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The use of improved variety, a proper seed rate, nutrient inputs and weed control may be responsible for the increase in grain production of sesame under CFLDs over FP. Similar yield enhancement in different crops in cluster frontline demonstrations were reported by Kumar et al, (2010) [4] in bajra; Kumar et al, (2020) [4] in sesame; Deka et al, (2021) [2] in rapeseed and Jakhar and Kumar (2022) [3] in green gram. During the three years of the investigation, an average extension gap and technological gap was recorded as 1.21 qha -1 of 2.63 qha -1 respectively.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The use of improved variety, a proper seed rate, nutrient inputs and weed control may be responsible for the increase in grain production of sesame under CFLDs over FP. Similar yield enhancement in different crops in cluster frontline demonstrations were reported by Kumar et al, (2010) [4] in bajra; Kumar et al, (2020) [4] in sesame; Deka et al, (2021) [2] in rapeseed and Jakhar and Kumar (2022) [3] in green gram. During the three years of the investigation, an average extension gap and technological gap was recorded as 1.21 qha -1 of 2.63 qha -1 respectively.…”
Section: Resultssupporting
confidence: 79%
“…However, higher benefit-cost ratio was observed in CFLD plots compare to the farmer's practice plot (Table 2). Hence, higher benefit cost ratios proved the economic viability of the cultivation practices and convinced the farmers to adopt the cultivation practices of new variety of rapeseed (Deka et al, 2021 and Kumar et al, 2022) [2,6] .…”
Section: Resultsmentioning
confidence: 99%
“…The variation in the technology index during the study period indicates of higher scope for further improvement in productivity of linseed in the district. Deka et al (2021) [8] also reported similar finding in rapeseed.…”
Section: Yield Gap Analysismentioning
confidence: 54%